Deep vein thrombosis associated with Staphylococcus aureus septicemia - Oberdorfer, Peninnah; Odell, Shaun; Kongthavonsakul, Kritsana (Biomedical Sciences and Clinical Medicine, 2024)
A 12-year-old boy was admitted to a provincial hospital with a history of high fever, right knee pain and swelling. He had fallen and injured both his knees one month previously, but did not seek treatment. He received intravenous antibiotics for seven days before being transferred to Chiang Mai University Hospital, with persistent knee pain and constant high fever. His blood cultures were positive for Staphylococcus aureus. Doppler ultrasound of the right leg showed venous thrombosis in the thigh, and a subsequent bone scan was positive for osteomyelitis adjacent to the thrombus. He was treated with anticoagulants. Three days after the transfer, he had severe right lower lobe pneumonia, and cloxacillin, clindamycin, and amikacin were prescribed. He showed clinical improvement markedly and was transferred back to the provincial hospital for planned long-term anticoagulation and antimicrobial treatment.